(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2019)
The term ‘gesture’ is often used for an action capable of conveying a meaning and, in this sense, it is related to the question of the origin of language. In this paper I rather focus on a concept of ‘gesture’ intended as the «supplement of an act» (Barthes), produced by an historical and cultural process (Berio) and representative of a «pure mediality» (Agamben). Such a different notion of gesture should not to be confused with a form of expression considered as an end in itself. In this perspective, I will try to think the artistic gesture not as bearer of meaning but as what is ‘beared’, i.e., as the non-communicative rest of previous acts of communication.